THE EFFECTIVENESS OF USING ILLUSTRATED FOLKTALE âTHE PRINCESS FARMERâ TO TEACH READING COMPREHENSION OF NARRATIVE TEXT A Quasi Experimental Research at the Tenth Year Students of SMK Diponegoro Juwana in the Academic Year of 2015/2016 - Sari, Badharul Nurtika (ELT Forum: Journal of English Language Teaching, 2016)
This article is about the use of illustrated folktale âThe Princess Farmerâ as a strategy to develop the studentsâ reading comprehension. In order to achieve the objectives of this research, the writer adopted a quasi-experimental research design. The subjects of this research were class X-AK 1 and X-AK 2 of SMK Diponegoro Juwana, in the academic year of 2015/2016 which consisted of 20 students in each class. In this study X-AK 2 was selected as the control group and X-AK 1 was selected as the experimental group. There were 5 meetings in this study. In the first meeting, there was pre-test, in the second, third, and fourth meetings there were treatments, and in the fifth meeting there was post-test. In order to collect data about studentsâ reading comprehension of narrative text, the writer used pre-test and post-test to know the studentsâ differences. Besides used test, this study also used questionnaire.Â  The result of this study showed that the use of illustrated folktale âThe Princess Farmerâ can measure studentsâ reading comprehension of narrative text well. Based on the result of this study, the writer concluded that the use of illustrated folktale âThe Princess Farmerâ gave a good contribution in English teaching and learning, especially in the area reading comprehension of narrative text.